Optimalisasi Sistem Penjadwalan Produksi Untuk Meminimalisir Keterlambatan Produksi Di PT Fahifa Prima Mandiri - Dwiky fadillah (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2023)
During the production process activities to get the best results, the production process activities need to be well planned. Production scheduling is one way to plan the activities of the production process. This research took place at PT Fahifa Prima Mandiri, at the time of direct research there were Lateness in meeting product requests from consumers. The purpose of this research is to optimize the scheduling of the production scheduling system used by the company by using the SPT, LPT, and EDD methods to minimize Lateness. FCFS is the method used by the company with a total Lateness of 65 days and an average Lateness of 9 days, the SPT method with a total Lateness of 51 days and an average Lateness of 7 days, the LPT method with a total Lateness of 89 days and an average Lateness 13 days, the EDD method with a total Lateness of 53 days and an average Lateness of 8 days. From the results of the calculation of several methods used the SPT method is the optimal method used, with the application of this method so that the production process at the company can be maximized.